PENGEMBANGAN MODEL PEMBELAJARAN KLINIK EXPERIENTIAL TERHADAP CAPAIAN PEMBELAJARAN PEMBELAJARAN KLINIK KEPERAWATAN GAWAT DARURAT MAHASISWA NERS - Helmi Setiawan, Arif; Yusuf, Ah.; Endang Nihayati, Hanik (Unusa Press, 2017)
Emergency nursing is a part of competences of profession program aimed to encourage the students to think critically to overcome the nursing problems which threaten the clients' lives. The learning method used in this stage is the experiential clinical learning. However, problems in achieving the learning outcomes still occur recently to result in low outcomes of clinical learning. This study used explanative method to describe the causal relationship among variables. This study involved all nursing students of the Faculty of Nursing and Midwifery of Unusa. 72 students were taken as the samples by using simple random technique. The endogenous variables were the students' characteristics, observation factors, thinking process, learning behaviors, and experiential clinical learning. The exogenous variables, on the other hand, were the outcomes of clinical learning in emergency nursing in ners students. The results of statistic test with Partial Least Square showed that all indicators and constructs variable were valid and significant. the significance test using structural model (t > 1,96), showed that the students' characteristics affected the observation factor, thinking process, and experiential clinical learning. The variable of observation factor affected the thinking process and learning behaviors. The variable of thinking process affected learning behaviors. The variable of learning behaviors affected experiential clinical learning. In addition, the variable of experiential clinical learning influenced the outcomes of clinical learning in emergency nursing in ners students. Experiential clinical learning model is categorized as a good model and has a prediction value if applied can improve learning achievement of clinical learning in emergency nursing in ners students. The dominant factors of successful experiential clinical learning are the characteristics of the students and learning behavior in ners students.